2013
DOI: 10.1111/ejn.12202
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of GLT‐1 in the R6/2 model of Huntington's disease does not worsen disease progression

Abstract: Excitotoxicity is thought to be important in the pathogenesis of Huntington’s disease (HD). Glutamate is the predominant excitatory neurotransmitter in the brain and excess activation of glutamate receptors can cause neuronal dysfunction and death. Glutamate transporters regulate the extracellular concentration of glutamate. GLT-1 is the most abundant known glutamate transporter and accounts for most of the glutamate transport in the brain. Administration of ceftriaxone, an antibiotic that increases the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 62 publications
1
41
2
Order By: Relevance
“…In addition to the studies in the hippocampus, more recent studies have demonstrated GLT-1 in presynaptic terminals the rat somatic sensory cortex (Melone et al, 2009), in the human cortex (Melone et al, 2011) and in the rat striatum (Petr et al, 2013). In a developmental study DeSilva et al (2012) determined the cellular and temporal expression of GLT-1 in the developing human cerebral cortex.…”
Section: Glt-1 Expression In Neuronsmentioning
confidence: 99%
“…In addition to the studies in the hippocampus, more recent studies have demonstrated GLT-1 in presynaptic terminals the rat somatic sensory cortex (Melone et al, 2009), in the human cortex (Melone et al, 2011) and in the rat striatum (Petr et al, 2013). In a developmental study DeSilva et al (2012) determined the cellular and temporal expression of GLT-1 in the developing human cerebral cortex.…”
Section: Glt-1 Expression In Neuronsmentioning
confidence: 99%
“…For example, Petr and colleagues described that reduced expression of GLT-1 in the R6/2 model does not worsen the progression of the phenotype. 51 Moreover, an in vitro experiment evaluating glutamate clearance in striatum showed normal and even accelerated striatal reuptake in the R6/2 model. 52 More recently, it was demonstrated that GLT-1 inhibition by DHK slows clearance rates to only a small fraction (~20%) of that produced by DL-TBOA, suggesting that non-GLT-1 transporters make a significant contribution to glutamate clearance, in particular when GLT-1 is dysfunctional, as occurs in HD.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that upregulation of GLAST function compensates for GLT‐1 deficiency might serve to clarify some controversies regarding GLT‐1 function in HD. For example, Petr and colleagues described that reduced expression of GLT‐1 in the R6/2 model does not worsen the progression of the phenotype . Moreover, an in vitro experiment evaluating glutamate clearance in striatum showed normal and even accelerated striatal reuptake in the R6/2 model .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that increase in the functional expression of GLT-1/EAAT-2, can improve the behavioral phenotype of the mouse model of HD (Miller et al, 2012;Estrada-Sanchez et al, 2009). To test the hypothesis that GLT-1/EAAT-2 expression critically affects the HD disease process, a novel mouse model R6/2 transgenic model that is heterozygous for the null allele of GLT-1/EAAT-2 and carries the double mutation was generated and it was found that the protein expression of total GLT-1/EAAT-2, as well as two of its isoforms, is decreased within the cortex and striatum of 12-week-old R6/2 mice (Petr et al, 2013). These study results suggested that changes in GLT-1/EAAT-2 expression or function can potentiate or ameliorate the progression of HD and it can serve as an important target for HD treatment (Petr et al, 2013).…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%
“…To test the hypothesis that GLT-1/EAAT-2 expression critically affects the HD disease process, a novel mouse model R6/2 transgenic model that is heterozygous for the null allele of GLT-1/EAAT-2 and carries the double mutation was generated and it was found that the protein expression of total GLT-1/EAAT-2, as well as two of its isoforms, is decreased within the cortex and striatum of 12-week-old R6/2 mice (Petr et al, 2013). These study results suggested that changes in GLT-1/EAAT-2 expression or function can potentiate or ameliorate the progression of HD and it can serve as an important target for HD treatment (Petr et al, 2013). Growing evidence also indicates that ascorbate (AA), an antioxidant vitamin, is released into striatal extracellular fluid when glutamate is cleared after its release from cortical afferents.…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%